2007
DOI: 10.1590/s0100-204x2007000300017
|View full text |Cite
|
Sign up to set email alerts
|

Formas de cobre em solos de vinhedos em função do pH e da adição de cama-de-frango

Abstract: Resumo -O trabalho teve como objetivo avaliar a distribuição de formas de cobre, em função do pH e da adição de cama-de-frango, em amostras da camada superficial (0 a 10 cm) de um Neossolo Litólico distrófico típico e de um Cambissolo Húmico alumínico típico, da região da Serra Gaúcha, cultivados por mais de 15 anos com parreirais que receberam aplicações sucessivas de produtos fitossanitários à base de cobre. Para avaliar os efeitos da variação do pH e do teor de matéria orgânica do solo nas formas de cobre, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
2
0
7
Order By: Relevance
“…The chemical affinity for the Cu(II) ion of humic substances is greater (Nachtigal et al, 2007), as observed here for the organically bound fraction. This affinity may be related to the larger ionic radius of copper, resulting in a smaller hydrated radius.…”
Section: Bioavailability and Mobility Of Heavy Metals In The Compostsupporting
confidence: 74%
“…The chemical affinity for the Cu(II) ion of humic substances is greater (Nachtigal et al, 2007), as observed here for the organically bound fraction. This affinity may be related to the larger ionic radius of copper, resulting in a smaller hydrated radius.…”
Section: Bioavailability and Mobility Of Heavy Metals In The Compostsupporting
confidence: 74%
“…Com o intuito de controlar essas doenças, as videiras são submetidas a aplicações sucessivas de fungicidas cúpricos que podem adicionar até 30 kg de cobre (Cu) ha -1 ano -1 ao sistema de produção de uvas (Nachtigall et al, 2007;Girotto et al, 2013).…”
Section: Introductionunclassified
“…The low value of MB-C under CO could be due to higher soil acidity and Al toxicity. Repeated applications of Cu fungicides for a long period cause Cu accumulation in soil (Nachtigall et al, 2007) which may decrease microbial activity. In CO, long-term fertilizer use can improve soil nutrient status, but can also increase soil acidification, by repeated N fertilizer applications (Aciego Pietri and Brookes, 2008).…”
Section: Discussionmentioning
confidence: 99%